ANALISIS SEKTOR UNGGULAN PEREKONOMIAN DI KABUPATEN PESISIR BARAT PROVINSI LAMPUNG SEBAGAI KABUPATEN TERTINGGAL - Hasyimi, Alifia; Affandi, Muhammad Irfan; Prasmatiwi, Fembriarti Erry (Jurnal Ekonomi Pembangunan, 2023)
This research aims to determine the leading sectors of the economy and the performance of the leading sectors in Pesisir Barat Regency. Research uses secondary data. Secondary data used in this research is Gross Regional Domestic Product (GRDP) based on constant prices for Lampung Province and Pesisir Barat Regency from 2018 to 2022. The analytical tools used in this research are Location Quotient (LQ) analysis and Shift-Share analysis. . The research results show that of the 17 business sectors in 2018-2022, there are 9 economic base sectors in Pesisir Barat Regency with an LQ value>1, namely the agriculture, forestry and fisheries sector; wholesale trade and vehicle repair sector, information and communications sector, real estate sector, corporate services, administration sector, educational services sector, health services sector and social activities and other service sectors. The economic growth of Lampung Province from 2018 to 2022 influenced the increase in PDRB of Pesisir Barat Regency by up to 10.76 percent with a total of IDR 316.72 billion with the agriculture, forestry and fisheries sector contributing the highest with a total contribution of IDR 159.86 billion